Gardnerella Exposures Alter Bladder Gene Expression and Augment Uropathogenic Escherichia coli Urinary Tract Infection in Mice - Gilbert, Nicole M.; O’Brien, Valerie P.; Waller, Chevaughn; Batourina, Ekatherina; Mendelsohn, Cathy Lee; Lewis, Amanda L. (Frontiers in Cellular and Infection Microbiology, 2022)
The anaerobic actinobacterium Gardnerella was first isolated from the bladder by suprapubic aspiration more than 50 years ago. Since then, Gardnerella has been increasingly recognized as a common and often abundant member of the female urinary microbiome (urobiome). Some studies even suggest that the presence of Gardnerella is associated with urological disorders in women. We recently reported that inoculation of Gardnerella into the bladders of mice results in urothelial exfoliation. Here, we performed whole bladder RNA-seq in our mouse model to identify additional host pathways involved in the response to Gardnerella bladder exposure. The transcriptional response to Gardnerella reflected the urothelial turnover that is a consequence of exfoliation while also illustrating the activation of pathways involved in inflammation and immunity. Additional timed exposure experiments in mice provided further evidence of a potentially clinically relevant consequence of bladder exposure to Gardnerella—increased susceptibility to subsequent UTI caused by uropathogenic Escherichia coli. Together, these data provide a broader picture of the bladder’s response to Gardnerella and lay the groundwork for future studies examining the impact of Gardnerella on bladder health.